2016
DOI: 10.1088/0741-3335/58/4/045019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regimes of cyclotron instability in the afterglow mode of minimum-Belectron cyclotron resonance ion source plasma

Abstract: Laulainen, J. (2016). Dynamic regimes of cyclotron instability in the afterglow mode of minimum-B electron cyclotron resonance ion source plasma. Plasma Physics and Controlled Fusion, 58 (4) AbstractThe paper is concerned with the dynamic regimes of cyclotron instabilities in nonequilibrium plasma of a minimum-B electron cyclotron resonance ion source operated in pulsed mode. The instability appears in decaying ion source plasma shortly (1 -10 ms) after switching off the microwave radiation of the klystron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…These electrons are eventually expelled into the loss cone. The comprehensive study of cyclotron instability in the afterglow of ECR discharge in argon plasma 10 has shown that instability is driven by the resonant interaction of hot electrons with slow extraordinary wave, which propagates quasi-parallel to the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…These electrons are eventually expelled into the loss cone. The comprehensive study of cyclotron instability in the afterglow of ECR discharge in argon plasma 10 has shown that instability is driven by the resonant interaction of hot electrons with slow extraordinary wave, which propagates quasi-parallel to the magnetic field.…”
Section: Discussionmentioning
confidence: 99%
“…The hump at higher energy is presumably linked to the B min value as discussed in the previous section. The hump at lower energy could be of similar origin, as a rich electromagnetic spectrum interacting with the electrons is generated during the instability event [6,15,16].…”
Section: Temporal Evolution Of the Leed During Single Instabilitmentioning
confidence: 99%
“…In the first case, slow extraordinary waves are excited most efficiently, which propagate at low angles to the magnetic field and interact with hot electrons distributed between the ECR heating zone and the center of the mirror trap. A similar mechanism of cyclotron instability, which explains the main properties of the dynamic spectra of pulses in the inherent electromagnetic radiation of the plasma in a magnetohydrodynamically stable trap of the "minimum-B" hexapole type, was proposed in [11]. A distinctive feature of excitation of a quasi-longitudinal slow extraordinary wave is the fact that the group velocity of the wave decreases as the plasma density grows, which results in an increase in the total instability growth rate even at fairly low densities of hot particles.…”
Section: Discussionmentioning
confidence: 86%
“…The use of high-power microwave radiation of gyrotrons allows one to increase the density and energy of the particles trapped in the mirror significantly (up to relativistic values), which allows one to study various regimes of wave excitation by energetic particles. (5), diagnostic camera (6), probe (7), CC-10 vacuum meter (8), microwave antenna (9), oscilloscope (10), turbomolecular pump (11), and forevacuum pump (12).…”
Section: Introductionmentioning
confidence: 99%